Assessment of quality of life in regions of Russia based on social media data. Issue 2 (July 2021) - Shchekotin, Evgeniy; Goiko, Viacheslav; Myagkov, Mikhail; Dunaeva, Darya
The article offers a new method of quality of life assessment based on online activities of social networks users. The method has obvious advantages (quickness of research, low costs, large scale, and detailed character of the obtained information) and limitations (it covers only the "digital population, " whereas the rural population is not included). The article dwells on the potential of social networks as a data source to analyze the quality of life; it also presents the results of an empirical study of online activities of the users of VK, the most popular Russian social network. Using the obtained data, the authors have calculated the quality of life index for 83 regions of the Russian Federation based on 19 parameters of economic, social, and political aspects of life quality.